CSI, crime scene investigation. The twelfth season [videorecording (DVD)] - Shue, Elisabeth; Danson, Ted, 1947-; Helgenberger, Marg; Fox, Jorja; Eads, George, 1967-; Guilfoyle, Paul; Szmanda, Eric; Langham, Wallace (Paramount Home Entertainment, 2012)
This is a fast-paced drama about a team of forensic investigators trained to solve crimes by examining the evidence. They are on the case 24/7, scouring the scene, collecting irrefutable evidence and finding the missing pieces that will solve the mystery.